Predictive Metabolic Suitability Maps for the Thermophilic Invasive Hydroid Pennaria disticha Under Future Warming Mediterranean Sea Scenarios - Bosch-Belmar, Mar; Piraino, Stefano; Sarà, Gianluca (Frontiers in Marine Science, 2022)
Temperature is a fundamental variable for all biological processes. It influences the metabolism and tolerance limits of all living organisms, affecting species phenology and distribution patterns. It also facilitates the spread of non-indigenous species and the proliferation and expansion of native outbreak-forming species. Pennaria disticha is a colonial benthic cnidarian reported to be invasive in different Indian and Pacific coastal areas, as well as a harmful member of fouling communities found in Mediterranean marine aquaculture farms. Using the most basal functional trait (i.e., thermal tolerance), we explored the potential of P. disticha to colonize different habitats across the Mediterranean Sea in future warming scenarios. Respiration rate was measured as a proxy of P. disticha metabolism under 12 different experimental temperatures. The obtained thermal tolerance dataset was used to create a thermal performance curve (TPC). We then scaled modeled curve to occurrence probability to map species potential metabolic habitat suitability and phenological shifts within the Mediterranean Sea when subjected to different warming scenarios. Prediction maps for future climatic conditions showed a potential temporal and spatial expansion of P. disticha in the Western and Central Mediterranean. The present data increases our understanding of the ecological performance and potential distribution of an invasive and outbreak-forming species. This information will contribute to the development of early warning systems and to the design and implementation of risk assessment and management plans.